Improvise 3-Level DTC of Induction Machine using Constant Switching Frequency Method by Utilizing Multiband Carrier - Sundram a/l Ramahlingam; Auzani Bin Jidin; Tole Sutikno; L. Logan Raj (International Journal of Power Electronics and Drive Systems (IJPEDS), 2016)
This paper presents the advantage of using optimal PI parameter tuning strategy of constant switching method in the three phase Direct torque control (DTC) scheme. The DTC system is known to offer fast decoupled control of torque and flux via a simple control structure. Nevertheless, DTC system has two major drawbacks, which are the variable inverter switching frequency and high torque output ripple. The major factorthat contributes to these problems the usage of hysteresis based comparators to control the output torque. The implementation of PI based constant switching method in DTC able to solve these problems while retaining the simple control structure of conventional DTC. The combination usage of 3-level CHMI in this system can further minimize the output torque ripple by providing greater number of vectors. This paper presents detail explanation and calculationof optimal PI parameter tuning strategyconsecutively to enhance the performance of 3-level DTC system. In order to validate the feasibility, the proposed method compared with convention DTC system via simulation and experiment results.